(untitled) (Journal of Kidney Cancer, 2021)
Primary synovial sarcoma (PSS) of the kidney is considered the rarest type of all renal sarcomas with specific chromosomal translocation t (X; 18) (p11.2; q11.2). We report the case of a 65-year-old man with no medical conditions who presented to the emergency department with sudden severe right flank pain associated with haemodynamic instability and haemorrhagic shock. Computed tomography (CT) of the abdomen and pelvis revealed a right renal mass. A right open radical nephrectomy was performed. Histopathology revealed a monophasic synovial sarcoma. The patient received six cycles of docetaxel and gemcitabine as adjuvant chemotherapy. No sign of recurrence was seen on a follow-up CT urogram. This rare tumour often presents atypically, and clear guidelines regarding appropriate treatment are lacking. Our case showed that treatment with docetaxel/gemcitabine after an open radical nephrectomy is promising.